Twenty-five years of India-ASEAN ties: An Assessment - Mishra, Rahul (AEI Insights, 2021)
India has more than two millennia old ties with the Southeast Asian countries, with a series of waves shaping its engagements with the ‘East’. However, India’s engagement with ASEAN begun only after the end of the Cold War. Since the launch of the Look East policy in 1992, by the then Indian prime minister P.V. Narasimha Rao, to 2018, when India and ASEAN have entered the twenty-sixth years of dialogue relations, their partnership has come a long way crossing several milestones. In the past twenty-five years, India has not only been able to resocialise itself in the politico-security regional architecture of Asia, but has also been able to successfully join several regional groupings related to security, trade and economic cooperation. India’s engagement with ASEAN has been elevated with Prime Minister Narendra Modi – led National Democratic Alliance (NDA) government’s announcement of upgrading Look East Policy to the Act East policy at 12th India-ASEAN Summit in Nay Pyi Taw, Myanmar in November 2014. India-ASEAN dialogue partnership completed twenty-five years in the year 2017. The same year, India and ASEAN also completed fifteen years of Summit level partnership and five years of their Strategic Partnership. This paper assesses twenty-five years of India’s engagement with ASEAN by analysing the level of institutional engagement between the two.